Association of body mass index-related single nucleotide polymorphisms with psychiatric disease and memory performance in a Japanese population. Issue 5 (7th December 2016) - Ninomiya-Baba, Midori; Matsuo, Junko; Sasayama, Daimei; Hori, Hiroaki; Teraishi, Toshiya; Ota, Miho; Hattori, Kotaro; Noda, Takamasa; Ishida, Ikki; Shibata, Shigenobu; Kunugi, Hiroshi
Abstract : Objective: Obesity is a risk factor for psychiatric diseases. Recently, a number of single nucleotide polymorphisms (SNPs) have been shown to be related to body mass index (BMI). In this study, we investigated the association of BMI-related SNPs with psychiatric diseases and one of their endophenotypes, memory performance, in a Japanese population. Methods: The subjects were 1624 patients with one of three psychiatric diseases (799 patients with major depressive disorder, 594 with schizophrenia, and 231 with bipolar disorder) and 1189 healthy controls. Memory performance was assessed using the Wechsler Memory Scale – Revised (WMS-R). Genomic DNA was prepared from venous blood and used to genotype 23 BMI-related SNPs using the TaqMan 5′-exonuclease allelic discrimination assay. We then analysed the relationships between the SNPs and psychiatric disease and various subscales of the WMS-R. Results: Three SNPs (rs11142387, rs12597579, and rs6548238) showed significant differences in the genotype or allele frequency between patients with any psychiatric diseases and controls. Furthermore, six SNPs (rs11142387, rs12597579, rs2815752, rs2074356, rs4776970, and rs2287019) showed significant differences in at least one subscale of the WMS-R depending on the genotypes of the healthy controls. Interestingly, rs11142387 near the Kruppel-like factor 9 ( KLF9 ) was significantly associated with psychiatric disease and poor memory function. Conclusions: We identified three and six BMI-related SNPs associated with psychiatric disease and memory performance, respectively. In particular, carrying the A allele of rs11142387 near KLF9 was found to be associated with psychiatric disease and poor memory performance, which warrants further investigations.